2018
DOI: 10.1158/2159-8290.cd-18-0877
|View full text |Cite
|
Sign up to set email alerts
|

Isoform Switching as a Mechanism of Acquired Resistance to Mutant Isocitrate Dehydrogenase Inhibition

Abstract: Somatic mutations in cytosolic or mitochondrial isoforms of isocitrate dehydrogenase (IDH1 or IDH2, respectively) contribute to oncogenesis via production of the metabolite 2-hydroxyglutarate (2HG). Isoform-selective IDH inhibitors suppress 2HG production and induce clinical responses in patients with IDH1- and IDH2-mutant malignancies. Despite the promising activity of IDH inhibitors, the mechanisms that mediate resistance to IDH inhibition are poorly understood. Here, we describe four clinical cases that ide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
137
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(146 citation statements)
references
References 25 publications
9
137
0
Order By: Relevance
“…In 2008 and 2009, mutations in genes encoding IDH1 and IDH2 were identified in the patients with glioblastoma and acute myeloid leukemia [53][54][55]. To date, IDH mutations have been reported in a variety of cancers, such as angioimmunoblastic T-cell lymphoma, myelodysplastic syndromes, myeloproliferative neoplasms, cholangiocarcinoma, and chondrosarcoma 56,57. Mutant IDHs lose their initial catalytic function for the conversion of isocitrate to α-KG, and gain the function for the production of 2-hydroxyglutarate (2HG) from α-KG and NADPH.…”
mentioning
confidence: 99%
“…In 2008 and 2009, mutations in genes encoding IDH1 and IDH2 were identified in the patients with glioblastoma and acute myeloid leukemia [53][54][55]. To date, IDH mutations have been reported in a variety of cancers, such as angioimmunoblastic T-cell lymphoma, myelodysplastic syndromes, myeloproliferative neoplasms, cholangiocarcinoma, and chondrosarcoma 56,57. Mutant IDHs lose their initial catalytic function for the conversion of isocitrate to α-KG, and gain the function for the production of 2-hydroxyglutarate (2HG) from α-KG and NADPH.…”
mentioning
confidence: 99%
“…Moreover, the progression of standard chemotherapy was associated with decreasing serum levels of 2HG, supporting a prognostic potential of 2HG (16). The ability of mutant-IDH1 inhibitors to provide effects in AML having mutant-IDH2 stems from the ability to switch their mutagenesis toward unmutated IDH1, which turns to be the right target (63,69).…”
Section: Hg As An Oncometabolitementioning
confidence: 94%
“…A specific IDH2 inhibitor was developed to bind to the IDH2 dimer interface (179). Surprisingly, tumors targeted by the specific IDH1 inhibitors have the ability to switch their mutagenesis toward unmutated IDH2, which is not affected, and vice versa (63,69).…”
Section: Fig 1 Typical Cancer Metabolism Related To the Formation Omentioning
confidence: 99%
“…They demonstrated that IDH1 mutant tumor cells were more sensitive to poly adenosine diphosphate ribose polymerase inhibitors, which provided new clues to a personalized treatment strategy. Harding et al . revealed isoform switching between mutant IDH1 and IDH2 as a mechanism involved in the acquired drug resistance to mutant IDH1/2 inhibitors by analyzing four patients.…”
Section: Applications Of Metabolomics In Clinical Pharmacologymentioning
confidence: 99%
“…They STATE of the ART demonstrated that IDH1 mutant tumor cells were more sensitive to poly adenosine diphosphate ribose polymerase inhibitors, which provided new clues to a personalized treatment strategy. Harding et al 73 revealed isoform switching between mutant IDH1 and IDH2 as a mechanism involved in the acquired drug resistance to mutant IDH1/2 inhibitors by analyzing four patients. By gene sequencing and 2-HG production monitoring, Intlekofer et al 74 showed the appearance of second-site IDH2 mutations in trans or formation of IDH dimer-interface mutations in cis might be another mechanism for the acquired drug resistance to mutant IDH inhibitors.…”
Section: Identification Of New Drug Targetsmentioning
confidence: 99%